2021
DOI: 10.3390/vaccines9121442
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Response of BNT162b2 and CoronaVac Platforms in Recovered Individuals Previously Infected by COVID-19 against SARS-CoV-2 Wild Type and Delta Variant

Abstract: Vaccinating recovered patients previously infected by COVID-19 with mRNA vaccines to boost their immune response against wild-type viruses (WT), we aimed to investigate whether vaccine platform and time of vaccination affect immunogenicity against the SARS-CoV-2 WT and Delta variant (DV). Convalescent patients infected by COVID-19 were recruited and received one booster dose of the BNT162b2 (PC-B) or CoronaVac (PC-C) vaccines, while SARS-CoV-2 naïve subjects received two doses of the BNT162b2 (CN-B) or CoronaV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…In one clinical study, Vasileiou et al reported that the effectiveness of primer-dose BNT162b2 was 85% at day 28-34 post-vaccination and then dropped to a level of 64% after 42 days post-vaccination [22]. Furthermore, from our previous study, the neutralizing activity in recovered patients with previous COVID-19 infection decreased significantly at week 6 after discharge [23]. Thus, the antibody response on day 56 might be lower than on day 28 in healthy individuals who have just received one dose of BNT162b2.…”
Section: Discussionmentioning
confidence: 69%
“…In one clinical study, Vasileiou et al reported that the effectiveness of primer-dose BNT162b2 was 85% at day 28-34 post-vaccination and then dropped to a level of 64% after 42 days post-vaccination [22]. Furthermore, from our previous study, the neutralizing activity in recovered patients with previous COVID-19 infection decreased significantly at week 6 after discharge [23]. Thus, the antibody response on day 56 might be lower than on day 28 in healthy individuals who have just received one dose of BNT162b2.…”
Section: Discussionmentioning
confidence: 69%
“…This is consistent with previous studies which showed a weaker NAb response among recipients of inactivated vaccines compared to mRNA vaccines. 19 , 24 , 32 , 39 , 40 , 47 However, we did not assess the T cell response, which may be important for the prevention of severe disease. Gilbert et al.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients in the vaccinated cohort were included in our previous study. 32 Under elimination strategy, all individuals with laboratory-confirmed COVID-19 are isolated in hospitals. For asymptomatic patients, the day of hospitalization was used as the date of symptom onset.…”
Section: Methodsmentioning
confidence: 99%
“…In another study of 288 participants [ 18 ], 99.3% of mRNA vaccine recipients were positive for IgG (VIDAS, Biomerieux Inc., Hazelwood, MO, USA) 6 weeks after the second dose of the vaccine, with mean titers of 515.5 BAU/mL, but only 85.7% of inactivated virus vaccine recipients were seropositive, with lower mean S-Ab titers around three-fold less than the titers of the mRNA vaccine group (170 BAU/mL). Even in patients with previous COVID-19 infection, a post-infection booster of mRNA vaccine (BNT162b2) caused 20.4–22.3-fold increases in virus neutralization titers, while the inactivated vaccine only resulted in a 1.8–2.2-fold increase [ 19 ]. Our findings are also supported by studies of patients who received heterologous dosing regimens [ 20 ], where a third dose of mRNA vaccine in patients who already received two doses of inactivated virus vaccine elicited a much more robust anti-receptor binding domain antibodies 14 days after inoculation (third dose inactivated virus vaccine: antibody geometric mean titer 1073 U/mL, third dose mRNA vaccine: antibody geometric mean titer 20,787 U/mL).…”
Section: Discussionmentioning
confidence: 99%